Knee Injuries in Downhill Skiers: A 6-Year Survey Study. Issue 1 (20th January 2014) - Shea, Kevin G.; Archibald-Seiffer, Noah; Murdock, Elizabeth; Grimm, Nathan L.; Jacobs, John C.; Willick, Stuart; Van Houten, Heather
Background: Knee injuries account for approximately one third of injuries in skiers. Researchers have proposed several mechanisms of knee injury in skiers. However, the frequencies of these mechanisms have varied in different studies. Purpose: To identify the most common knee injury mechanisms in recreational downhill skiers and to assess injury frequencies across several demographics. Study Design: Descriptive epidemiology study. Methods: Over 6 ski seasons, 541 patients with acute knee injuries completed a survey. Patients selected 1 of 6 injury classifications; age, sex, height, weight, years of experience, ability level, and ski binding release were also recorded. Results: The overall injury distribution was valgus–external rotation (32.9%), phantom foot (22.5%), hyperextension (19.0%), boot induced (7.8%), collision (2.2%), and other (15.6%). The phantom foot mechanism was most common in ages 30 to 40 years (36.3% of all injuries within this mechanism; P < .01). Children and adults showed no significant difference in distribution of injury mechanism. Of 80 youth skiers, valgus–external rotation was most common (35.4%), followed by phantom foot (25.3%). Adult and youth skiers who identified as "advanced" skiers had a higher prevalence of valgus–external rotation than did less experienced skiers (51.5% of total valgus injuries; P < .01). Bindings released in 19.3% in adults and 53.7% in youths ( P < .01) during injury. Female skiers comprised 60.0% of total respondents, but only 39.7% of injuries occurred in female children ( P < .01). Conclusion: Valgus–external rotation is the most common injury mechanism for recreational skiers in general. Previous studies have suggested that the phantom foot injury is the most common injury, but in this series, it was the second most common, representing 22.5% of injuries in this study. Individuals between the ages of 30 and 40 years showed an increased risk for the phantom foot mechanism, and the prevalence of injuries was significantly higher for females compared with males in this cohort ( P < .01). Children and adults appear to have similar mechanisms for ski-related knee injuries, with valgus–external rotation being most common and advanced skiers having the highest frequency of this mechanism. Binding release was more likely to occur in youth skiers.